Binary data analysis of randomized clinical trials with noncompliance - Lui, Kung-Jong; Wiley InterScience (Online service). (Chichester, West Sussex, U.K. John Wiley & Sons, 2011)
"This book provides a systematic and organized approach to analyzing data for a RCT with noncompliance under the most frequently-encountered situations, including parallel sampling, stratified sampling, cluster sampling, parallel sampling with subsequent missing outcomes, and a series of dependent binomial sampling for repeated measurements"--Provided by publisher.
Electronic reproduction.
Keywords: Clinical trials -- Statistical methods; Drugs -- Testing -- Statistical methods; Electronic books